INDICATORS OF GOOD PRINCIPAL LEADERSHIP BASED ON PRINCIPAL, TEACHERS, AND ADMINISTRATION STAFF PERSPECTIVES IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Senjaya, Aan Juhana (Universitas Pendidikan Indonesia, 2019)
Research relating to the leadership of principals in Indonesia generally uses indicators from various theories and literatures. In fact, principal, teachers and staff who are directly involved with the activities of school principals, of course, they have their own criteria and indicators relate to good principal leadership. This study aims to explore and find the good principal leadership indicators based on principals, teachers, and administration staff perspectives. An open question about the characteristics of a good principal ledership was asked to 124 respondents (12 principals, 93 teachers, and 19 administrative staff). The answer is directed and written at least 3 characteristics words. Furthermore, 670 statement as answers were analyzed qualitatively to take the similarity of meaning and there are 36 Statements with different meaning. Quantitative analysis is done to sort the indicators based on Response Indeks (RI). The results show there are 29 indicators, namely: Wise, Honest, To be responsible, Role models, Discipline, Assertive, Charimatic, Mastering IT, Fair, Smart, Visionary, Transparent, Democratic, Responsive, Open, Friendly, Protect, Humble, Communicative, Motivator, Souled leader, Able to solve problems, Creative, Loyal, Professional, Social soul, Self-Cofidence, and Trustful.